Reclaiming pietism: retrieving an evangelical tradition - Olson, Roger E. (William B. Eerdmans Publishing Company, 2015)
Defining and redefining Pietism : how a good word got a bad reputation -- Pietist backgrounds : precursors and cousins of Pietism -- Reforming the Reformation : classical Pietism's beginnings, part I -- Reforming the Reformation : classical Pietism's beginnings, part II -- A portrait of Pietism : its authentic hallmarks -- Where Pietism flourished on new soil : Great Britain and North America -- Pietism for a new era : the re-invention of Pietism in the nineteenth century -- Contemporary appropriations of the Pietist impulse : four exemplars -- Conclusion: Pietism as a way of doing evangelical theology